2010
DOI: 10.1016/j.otohns.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the diagnosis of chronic rhinosinusitis based on clinical guidelines and endoscopy

Abstract: In patients meeting current guideline symptom criteria for CRS, the addition of nasal endoscopy improves diagnostic accuracy and should be emphasized as an early diagnostic tool. Diagnostic endoscopy may help reduce the use of CT, reducing costs and radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 19 publications
6
118
1
5
Order By: Relevance
“…655,656 Evidence has shown combining 2 or more symptoms together along with objective findings of disease (imaging, endoscopy) substantially increases diagnostic specificity and positive predictive value. 9,15,657 Although the original guidelines used major and minor criteria, 11 there has been no consensus or evidence whether this categorization is based on prevalence, sensitivity, or specificity of symptoms. As a result, the present definition includes the most sensitive symptoms as part of the diagnosis.…”
Section: Viid Crssnp: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…655,656 Evidence has shown combining 2 or more symptoms together along with objective findings of disease (imaging, endoscopy) substantially increases diagnostic specificity and positive predictive value. 9,15,657 Although the original guidelines used major and minor criteria, 11 there has been no consensus or evidence whether this categorization is based on prevalence, sensitivity, or specificity of symptoms. As a result, the present definition includes the most sensitive symptoms as part of the diagnosis.…”
Section: Viid Crssnp: Diagnosismentioning
confidence: 99%
“…Prior studies comparing symptoms against a CT gold standard have suggested the specificity of symptoms in the range of 2% to 12% and positive predictive values ranging between 35% and 54%. 7,655,657 r Aggregate Grade of Evidence: B (Level 2b: 8 studies;…”
Section: Because Of Limited Data Crswnp and Crssnp Are Combined In Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic rhinosinusitis (CRS) is a common disease of the nasal cavity and sinuses that affects millions of people worldwide (1). CRS can be divided into two subtypes: CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP) (2).…”
Section: Introductionmentioning
confidence: 99%